Tracheal agenesis: the importance of teamwork in an uncommon pathology, challenging diagnosis, and high mortality—a case report - Fernández Monteagudo, Belén; Piris Borregas, Salvador; Niño Díaz, Lidia; Carbayo Jiménez, Tania; Morante Valverde, Rocío; Redondo Sedano, Jesús Vicente; Moral Pumarega, Maria Teresa (Frontiers in Pediatrics, 2024)
Introduction: We present the case of a patient with an unexpected postnatal diagnosis of tracheal agenesis, a severe and rare pathology with fewer than 200 cases documented in the literature, typically diagnosed postmortem. In our instance, early diagnosis was achieved through collaborative efforts and teamwork among various professionals. We provide illustrative images and videos to assist colleagues in identifying this congenital anomaly. Case Presentation: The patient is a term newborn with prenatal indicators of polyhydramnios and a single umbilical artery. Upon birth, the infant exhibited severe respiratory distress, and the orotracheal intubation via direct laryngoscopy was unfeasible. Consequently, an urgent fibrobronchoscopy was conducted by pediatric surgeons, resulting in the diagnosis of tracheal agenesis with tracheoesophageal fistula and the placement of a directed endotracheal tube. This intervention facilitated temporary ventilation until parental consensus on management was achieved. Subsequent to a multidisciplinary consultation, it was determined to proceed with extracorporeal membrane oxygenation (ECMO). Regrettably, the patient experienced a prolonged refractory cardiorespiratory arrest and died after seven hours of life in his mother’s arms. Conclusion: Teamwork in neonatology is indispensable when addressing emergent pathologies. In our experience, multidisciplinary management, including anesthesiologists and pediatric surgeons, should be contemplated in complex scenarios.